Syndrome of inappropriate secretion of antidiuretic hormone (SIADH) associated with lateral medullary syndrome: case report and literature review. Issue 1 (December 2016) - Nakano, Hiroro; Yanase, Daisuke; Yamada, Masahito
Abstract Background Only one case of syndrome of inappropriate secretion of antidiuretic hormone with lateral medullary syndrome has been reported so far. We report a case of lateral medullary syndrome showing syndrome of inappropriate secretion of antidiuretic hormone and analyze the pathomechanism underlying its clinical features. Case presentation A 67-year-old man was admitted to our hospital for dizziness, dysarthria, and dysphagia. He was diagnosed with lateral medullary syndrome based on the neurological examination and brain magnetic resonance imaging. Horner syndrome was absent. Asymptomatic hyponatremia appeared 9 days after admission and the patient was diagnosed with syndrome of inappropriate secretion of antidiuretic hormone. Fluid restriction and intravenous furosemide injection improved the hyponatremia. Conclusion Lateral medullary syndrome could be associated with syndrome of inappropriate secretion of antidiuretic hormone.